Corporate social responsibility : readings and cases in a global context - Spence, Laura J., 1968-; Crane, Andrew, 1968; Matten, Dirk (London, New York Routledge, 2014)
Modern business is obliged to meet increasingly demanding ethical, environmental, legal, commercial, and public standards as defined by wider society. Corporate Social Responsibility (CSR) has therefore become an important consideration for managers at all levels, as well as one of the most vibrant areas of study and research in the field of business and management. This important new book provides a comprehensive and student-centred introduction to the key themes and issues currently being addressed in CSR around the world.
Keywords: Empresas -- Responsabilidad social